The Conflict of Justice and Legal Certainty in the National Criminal Code: A Middle Way - Sari, Agustina Indah Intan; Frans, Mardian Putra (Magister Hukum Universitas Semarang, 2024)
The research discusses the unclear meaning of Article 53 paragraph (2) of Law No. 1 of 2023 which states that